The relationship between quality of work life and job performance among lecturers in private colleges in Kuantan / Abdullah Sani Mazlan - Mazlan, Abdullah Sani (2010)
This research is to discover whether the quality of work life among the lecturers in private colleges has an impact in their work performance. The literature provided discusses the two variables of quality of work life and job performance. Quality of work life as independent variables (i.e. remunerations, working environment, job security and safety and job satisfaction) was tested to indicate whether there is a relationship or not with job performance as a dependent variable. Data were collected from 161 lecturers who are attached with several private colleges in Kuantan such as Kolej Cosmopoint, Kolej Ikip, Kolej Islam Sultan Haji Ahmad Shah, Kolej Olympia, Kolej Pacific, Kolej PSDC and Kolej Shahputra. The study showed that each aspects of quality of work life (QWL) has an effect on job performance. The result depicts that all of the four aspect of quality of work life have significant and positive relationship with job performance. Finally, the study found that the quality of work life framework by Hayrol et al. was suitable to be used in studying lecturers job performance and could represent an appropriate framework for studying quality of work life in private colleges in Kuantan, Pahang.